Development of the three-tiers diagnostic test and students level of understanding and misconception in genetics - Nurhazwani Mohd Shukri (2022)
This study is aimed to develop a valid and reliable three-tiers diagnostic test in genetics. The study also aimed to assess pre-university students level of understanding and misconception in genetics by utilising the developed test and to explore the misconception issue. It has employed a developmental design involving adaptation, validation and pilot study phase. The test named as Three-Tiers Diagnostic Test in Genetics (3-TDTG) consists of 15 questions was administered in the empirical study. Ten biology experts and 30 pre-university students were involved in the developmental phase, whereas 455 students of a matriculation college in northern peninsular Malaysia involved in the empirical study. Seven of them were purposely selected to be interviewed, along with six biology lecturers. The findings suggest the 3-TDTG to be valid with S-CVI values of 0.98 and 0.96 for face and content validity respectively. The false positive and negative value was minimised to 10.90% and 5.44%. Excellent construct validity was observed as Pearson correlation suggests a significant moderate positive relationship between the U2 and CS score, r(453) =.44, p<.01. Reliability of 3- TDTG is high with Cronbachs alpha value of 0.78, items mean difficulty index of 0.37, and mean point-biserial correlation of 0.38. Students exhibited highest understanding on monohybrid inheritance and allele concept (U3=86.15%) while dihybrid inheritance recorded the highest misconception (M3=18.9%). The interview analysis suggests the misconception was due to complex genetics terminologies, complex application of multilevel thinking, dissociation of meiotic knowledge, memorisation and familiarisation, and poor internalisation of new concepts. To conclude, 3-TDTG is valid and reliable to asses students genetics understanding and misconception, and the misconception issues were successfully addressed. Finally, the study has the implication on teachers where they can utilise 3-TDTG prior to the lesson for better lesson planning, while researcher can employ the test to expand the knowledge in wider scope.